The economic benefits of mitigating the risk of unplanned power outages - Majid Hashemi; Glenn P. Jenkins (Queen's University, Department of Economics, 2021)
This paper takes on a novel perspective to the overloading of distribution substations by considering the common-pool characteristics of electric infrastructure capacity. Using firmand substation-level data from a sample of Nepalese firms, the results provide evidence of common-pool resource (CPR) problems across substations' ownership boundaries: firms with captive substations experience fewer and shorter unplanned outages than firms connected to shared substations. Based on these findings, private investments in captive substations emerge as a coping mechanism against unreliable electricity supply. Lastly, an appraisal framework for such investments is developed and used to quantify the economic benefits to Nepal's economy.
Keywords: Q41; D61; H4; L43; 330; Opportunity cost of power outages; electricity reliability; common-pool resource; electricity